Synthesis, Structure And Antimicrobial Properties Of New Silver(I)- And Palladium(Ii)-N-Heterocyclic Carbene Complexes Derived From [Benz]Imidazol-2-Ylidenes - Asekunowo, Patrick O. (2015)

(untitled)
Tesis ini melaporkan sintesis, struktur dan ciri antimikrob pelbagai kompleks argentum (I)- dan palladium(II)-NHC mengandungi ligan [benz]imidazolin-2-ilidena. Hasil penemuan penyelidikan ini dibentangkan dalam empat bab. Dua jenis garam [benz]imidazolium dengan gantian yang berlainan telah disediakan. Jenis yang pertama ialah garam mono-[benz]imidazolium (1-15) yang berteraskan eter, nitril dan alil. Kesemua garam mudah diubah dengan menggunakan gantian akil/akil aril pada posisi ketiga pada gelang [benz]imidazolium. Manakala jenis yang kedua ialah garam bis-[benz]imidazolium (16-25) terbitan sistem terangkai propil, piridina dan para-xilena. Kompleks disediakan melalui tindakbalas in situ Ag2O dengan garam [benz]imidazolium sepadan secara mempelbagaikan nisbah molar logam kepada garam, menghasilkan dua puluh lima kompleks Ag(I)-NHC (26-50) yang baru. This thesis reports the synthesis, structure and antimicrobial properties of various silver(I)- and palladium(II)-NHC complexes bearing [benz]imidazolin-2-ylidene ligands. The findings of the research are presented in four chapters. Two types of [benz]imidazolium salts with different substituents were prepared. The first type is mono-[benz]imidazolium salts (1-15) with ether, nitrile and allyl functionalities. They are conveniently tuned, using different alkyl/alkyl aryl substituents at the 3- position of the [benz]imidazolium ring. While the second type is bis- [benz]imidazolium salts (16-25) derived from propyl, pyridine and para-xylene linked systems. The complexes were prepared by in situ reaction of Ag2O with the corresponding [benz]imidazolium salts by varying the metal to salt molar ratio, resulting in the isolation of twenty five new Ag(I)-NHC complexes (26-50).